COVID-19 Toes and Other Skin Lesions During the Pandemic: Emerging Entities?. (December 2022) - Vas, Prashanth R. J.; Georgiadis, George S.; Papanas, Nikolaos
There is accumulating evidence to indicate an association between coronavirus infectious disease 2019 (COVID-19) and clusters of incident cutaneous eruptions. Of these, chilblains-like perniosis have received widespread medical and media attention. These typically affect the toes, and have been called "COVID-toes." Other acral lesions such as large bullae have also been reported. However, a definitive causal relationship with the severe acute respiratory syndrome coronavirus 2 has not yet been definitively proven, nor has a pathogenic mechanism been established. These episodes are self-limiting, but we need to know whether long-term sequelae exist.